2015
DOI: 10.7567/apex.8.073006
|View full text |Cite
|
Sign up to set email alerts
|

Persistent spin helix on a wurtzite ZnO$(10\bar{1}0)$ surface: First-principles density-functional study

Abstract: The persistent spin helix (PSH) that has been widely and exclusively studied in zinc-blende structures is revealed for the first time on the surface of a wurtzite structure. Through first principles calculations of the surface of ZnOð1010Þ, a quasi-one-dimensional orientation of the spin textures is identified. Furthermore, the wavelength of this particular PSH is smaller than that observed in various zinc-blende quantum well structures, thus indicating that wurtzite-structured surfaces are suitable for spintr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In the case of ZnO (1010)-2H surface, we find that the electric polarization in the in-plane ∆P y and out-of-plane . 22 The larger value of the in-plane electric polarization ∆P y indicates that the electric field in the in-plane direction E y is enhanced, which is expected to induce Thus far, we have found that hydrogen termination on the ZnO (1010) surface induces a Rashba effect with a strong anisotropic character. Here, we find that the Rashba coupling parameter (α R ) has some substantial values, estimated from the band dispersion in Fig.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…In the case of ZnO (1010)-2H surface, we find that the electric polarization in the in-plane ∆P y and out-of-plane . 22 The larger value of the in-plane electric polarization ∆P y indicates that the electric field in the in-plane direction E y is enhanced, which is expected to induce Thus far, we have found that hydrogen termination on the ZnO (1010) surface induces a Rashba effect with a strong anisotropic character. Here, we find that the Rashba coupling parameter (α R ) has some substantial values, estimated from the band dispersion in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, the strong anisotropic character of Rashba splitting predicted in the present study should ensure that carriers have an extended spin lifetime, [41][42][43] which is promising for energy-saving spintronics devices. 22 Therefore, this finding opens a possibility to realized spintronics devices using oxide electronic surface materials.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations